Giant cerebral cavernous malformation causing raised intracranial pressure in an adult: Case report and review of literature - Rajeev Sharma; Dwarakanath Srinivas; Somanna Sampath (Indian Journal of Neurosurgery)
Giant cerebral cavernous malformations (GCCMs) are very rare malformations in adults, and they rarely present with raised intracranial pressure due to obstructive hydrocephalus. Around 20 cases of GCCMs have been reported in available literature. We report such a case, discuss and review the available literature regarding this eminently treatable group of vascular malformations.